(untitled) (Economic and Political Thought, 2012)
The creators of the social market economy wanted to formulate a pattern of economic policy that would help to achieve effective implementation of a material goal of the economy without disturbing socially accepted values such as freedom and justice. In their opinion it is possible to achieve this goal thanks to the policy of creating an economic order and leaving the economic process to the market entities. However, the research conducted by the mainstream economists shows several deficiencies that do not allow it to function fully effectively. One of those deficiencies is the problem of appropriation, especially its effects. The companies’ desire to maximize profits makes those companies give up their investments in case their investments may be appropriated. That results in a deterioration of economic effectiveness and the creation of economic rents in some groups of entrepreneurs. The article is aimed at a closer analysis of the appropriation problem and possibilities of overcoming it in the social market economy – with the use of means that do not violate its fundamental principles. Moreover, overcoming the problem of appropriation creates opportunities for more effective use of discretional means in the situation of deep economic depression without the violation of those fundamental principles.